The majority of CD1d‐sulfatide‐specific T cells in human blood use a semiinvariant Vδ1 TCR - Bai, Li; Picard, Damien; Anderson, Brian; Chaudhary, Vinod; Luoma, Adrienne; Jabri, Bana; Adams, Erin J.; Savage, Paul B.; Bendelac, Albert (European journal of immunology, 2012)
αβ T‐cell lines specific for sulfatide, an abundant myelin glycosphingolipid presented by various CD1 molecules, have been previously derived from PBMCs of patients with demyelinating diseases such as multiple sclerosis (MS) but also from healthy subjects. Using an unbiased tetramer‐based MACS enrichment method to enrich for rare antigen‐specific cells, we confirmed the presence of CD1d‐sulfatide‐specific T cells in all healthy individuals examined. Surprisingly, the great majority of fresh sulfatide‐specific T cells belonged to the γδ lineage. Furthermore, these cells used the Vδ1 TCR variable segment, which is uncommon in the blood but predominates in tissues such as the gut and specifically accumulates in MS lesions. Recombinant Vδ1 TCRs from different individuals were shown to bind recombinant CD1d‐sulfatide complexes in a sulfatide‐specific manner. These results provide the first direct demonstration of MHC‐like‐restricted, antigen‐specific recognition by γδ TCRs. Together with previous reports, they support the notion that human Vδ1 T cells are enriched in CD1‐specific T cells and suggest that the Vδ1 T‐cell population that accumulates in MS lesions might be enriched in CD1‐sulfatide‐specific cells.